A rare case of leiomyoma over the nose - Harinatha Sreekar; P Sudarshan; Nithya Raghunath; Vithal Malmande (Our Dermatology Online, 2014)
Leiomyoma is an uncommon smooth muscle tumor on the face. Its occurrence is common in the uterus. Though skin lesions have been reported, they are clinically difficult to diagnose as they have features similar to various other swelling. Here we present one such case of leiomyoma over nose that can often be misleading.